Effect of tadalafil on erectile dysfunction in male patients with diabetes mellitus - Popović Srđan; Nale Đorđe; Dabetić Marija; Matanović Dragana; Dimitrijević-Srećković Vesna; Milić Gordana; Gostiljac Draško; Vujović Svetlana; Antonijević Nebojša; Nišić Tanja; Đorđević Predrag (Vojnosanitetski Pregled)
Background/Aim. During the first 10 years over 50% of diabetes patients develop erectile dysfunction (ED). It is more severe and resistant to therapy than in male patients with normal glucoregulation. The purpose of this pilot study was to estimate the tadalafil (Cialis) efficacy and safety in male patients with diabetes mellitus (DM), together with moderate to severe ED. Methods. The study included 30 male patients with diagnozed type 1 or type 2 DM together with ED. ED was estimated through the International Index of Erectile Function (IIEF-6), Sexual Encounter Profile (SEP) questionnaire and prostaglandin test, at the beginning of the research and three months after the 20 mg tadalafil therapy initiation, once a week (on Fridays). Glycosylated haemoglobin in blood (HbA1c) values were also monitored. According to the ED severity (IIEF values at the beginning of the therapy) the patients were divided into 2 groups. The previous experience with sildenafil citrate (Viagra) and prostaglandin E1 intracavernous therapy was recorded. Results. Tadalafil significantly improved ED (p < 0.001) for 7.40 points of the IIEF score, i.e. for 58% and 60% towards SEP2 and SEP3 questionnaire, respectively. Compared to the previous ED therapy subjectively better tadalafil experience was recorded. Each group experienced a significant improvement in IIEF score (p < 0.001), more significantly in the group 2 (8.26±1.49 points) compared with the medium improvement in the group 1 (6.27±1.35 points). After three months HbA1c values decreased for 2.26±1.62 (p < 0.001). Conclusion. Tadalafil is an effective tool for treating ED in diabetes patients. In some situations tadalafil application could replace prostaglandin test. The sexual sphere motivation leads to the improvement of glucoregulation in DM patients. .